1998
DOI: 10.1136/gut.42.6.856
|View full text |Cite
|
Sign up to set email alerts
|

Serum and liver HCV RNA levels in patients with chronic hepatitis C: correlation with clinical and histological features

Abstract: (Gut 1998;42:856-860)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
62
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 32 publications
(22 reference statements)
11
62
0
Order By: Relevance
“…1 The factors that determine the severity of liver disease in chronic HCV infection and their relative importance are not fully defined. Serum HCV RNA levels, as a proxy measurement of viral replication, correlate poorly with disease severity, 3,4 whereas conflicting data exist as to whether measurements of intrahepatic HCV replication correlate better with liver injury. [3][4][5][6][7][8][9] Virus-host interactions are also thought to be a significant cause of liver injury.…”
Section: Hronic Infection With Hepatitis C Virus (Hcv) Ismentioning
confidence: 99%
“…1 The factors that determine the severity of liver disease in chronic HCV infection and their relative importance are not fully defined. Serum HCV RNA levels, as a proxy measurement of viral replication, correlate poorly with disease severity, 3,4 whereas conflicting data exist as to whether measurements of intrahepatic HCV replication correlate better with liver injury. [3][4][5][6][7][8][9] Virus-host interactions are also thought to be a significant cause of liver injury.…”
Section: Hronic Infection With Hepatitis C Virus (Hcv) Ismentioning
confidence: 99%
“…As a whole, these studies have failed to find a consistent relationship between serum titers and the degree of hepatic injury. [2][3][4] The ratios of HCV genome RNA in liver and serum compartments are significantly different among chronically infected patients. 2,[5][6][7][8] These reports suggest that hepatic injury, serum titers, and intrahepatic viral replication do not display a linear relationship during chronic hepatitis C infection.…”
Section: Hepatitis C Virus (Hcv) Replication At the Cellular Level Ismentioning
confidence: 99%
“…[33][34][35][36] One recent, compelling study measured and found a positive correlation between serum and liver levels of HCV RNA, but neither level correlated with either ALT activity or histological abnormality. 27 Similarly, in another recent study that found a strong correlation between HCV RNA and core antigen levels, no association was identified between the levels of these two viral markers and fibrosis, necroinflammation, or steatosis on liver biopsy, viral genotype, ALT concentration, or alcohol consumption. 28 So, what accounts for the findings by the present authors of a strong association between HCV RNA levels and ESLD, given that the weight of evidence seems to contradict this relationship?…”
mentioning
confidence: 93%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Most have been single, cross-sectional studies that have not, however, tracked the long-term significance of the findings, as was done in the study reported in this issue of HEPATOLOGY. The results have been varied: the majority found no relationship whatsoever with liver disease severity [19][20][21][22][23][24][25][26][27][28][29] ; some identified increased hepatic inflammation without an impact on fibrosis [30][31][32] ; and a few identified increasing histological severity with increasing levels of virus. [33][34][35][36] One recent, compelling study measured and found a positive correlation between serum and liver levels of HCV RNA, but neither level correlated with either ALT activity or histological abnormality.…”
mentioning
confidence: 99%